The Role of Social Worker in High Schools: A Case Study from Thailand - Daraha Kanlaya (Research Developments in Arts and Social Studies Vol. 5, 2022)
The present study determines the role of Social Worker in High Schools in Thailand. The social workers would prefer to solve the psychosocial aspects among high school students to use the internet in Pattani. Currently, social workers in Thailand have not been considered to help schools deal with high school students who are facing Psychosocial Aspects and Academic Performance. The community suggests that the community be explored, which includes students, school directors, teachers, police officers, parents, and internet cafe owners. Their replies in the interviews are compared to issues of social well-being and internet use among Pattani high school students. The need for social workers in Pattani schools is universally agreed upon by those questioned and discussed in focus groups. School social workers can assist high school kids in using the internet responsibly, and they can be more effective in resolving issues that arise as a result of internet use. The research should be structured to compare two test groups. There should be a comparison between high school students who study through the Internet and those who learn through traditional methods.